2010
DOI: 10.1111/j.1468-3083.2010.03906.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus typing of warts and response to cryotherapy

Abstract: This study demonstrates that HPV type can be determined from wart parings. HPV-2 related viruses are the prevalent HPV types causing common warts on the hands and feet in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
1
23
2
Order By: Relevance
“…6,8,9 However, Hagiwara et al, Chen et al, and Tomson et al found no relation with age. 6,7,11 The reasons for this are not clear, but may be influenced by their study population with a very low prevalence of HPV 2/27/57 6,7 or HPV 1. 11 In the current study, the presence of multiple HPV types was detected in 16% of all swabs, which is more than reported in other studies 6,9,20,24,25 ; this is probably due to our HSL-PCR/MPG method which is specifically capable of detecting multiple HPV types per sample.…”
Section: Comparison With Literaturementioning
confidence: 89%
See 2 more Smart Citations
“…6,8,9 However, Hagiwara et al, Chen et al, and Tomson et al found no relation with age. 6,7,11 The reasons for this are not clear, but may be influenced by their study population with a very low prevalence of HPV 2/27/57 6,7 or HPV 1. 11 In the current study, the presence of multiple HPV types was detected in 16% of all swabs, which is more than reported in other studies 6,9,20,24,25 ; this is probably due to our HSL-PCR/MPG method which is specifically capable of detecting multiple HPV types per sample.…”
Section: Comparison With Literaturementioning
confidence: 89%
“…6,7,11 The reasons for this are not clear, but may be influenced by their study population with a very low prevalence of HPV 2/27/57 6,7 or HPV 1. 11 In the current study, the presence of multiple HPV types was detected in 16% of all swabs, which is more than reported in other studies 6,9,20,24,25 ; this is probably due to our HSL-PCR/MPG method which is specifically capable of detecting multiple HPV types per sample. 20 These warts with multiple HPV types were analysed separately from the warts with a single HPV type, since combining them would dilute associations with patient characteristics and reduce the clarity of interpretation.…”
Section: Comparison With Literaturementioning
confidence: 89%
See 1 more Smart Citation
“…Certain strains have predilections for particular body areas, such as HPV-2, HPV-27, and HPV-57 for warts on the hands and feet (Tomson et al 2011 ). Although warts often appear as solitary, defined lesions, the virus may be present at distant sites and may persist for many years.…”
Section: Introductionmentioning
confidence: 99%
“…For something that often seems fairly innocuous, warts are responsible for some 20 % of all dermatology referrals [44]. Different subtypes of HPV create different types of lesions and affect different areas of the body, with HPV-2, HPV-27, and HPV-57 frequently causing common warts on hands and feet [45]. Treatment for cutaneous warts varies depending on location, morphology, and the patient's wishes.…”
Section: Wartsmentioning
confidence: 99%